SURG-10. The evolving role of neurosurgery for central nervous system metastases in the era of personalized medicine. (9th August 2021) - Karschnia, Philipp; Rhun, Emilie Le; Grau, Stefan J; Preusser, Matthias; Soffietti, Riccardo; van den Bent, Martin; Vogelbaum, Michael; von Baumgarten, Louisa; Westphal, Manfred; Weller, Michael; Tonn, Joerg-Christian
Abstract: Background: Novel therapies translating into improved survival of patients with advanced cancer have emerged. The number of metastases in the central nervous system is therefore seen to increase. Neurosurgery assumes an expanding role within multi-disciplinary care structures for such patients. Methods: We performed a comprehensive literature review on the current status of neurosurgery for brain metastases patients. Based on the extracted data, we developed a review from experts in the field on the role of brain metastasis surgery in the era of personalized medicine. Results: Traditionally, three metastases were considered the cutoff to offer surgical resection. With respect to the clinical status, the resection of a symptomatic mass may nowadays be considered even in presence of multiple tumors in a multimodal setting: surgical resection of brain metastasis provides immediate relief from mass effect-related symptoms and histology in case of unknown primary tumor; surgery may help stabilizing the disease, thus enabling further therapy; and in situations where immunotherapy is considered and non-surgical management would require long-term steroid administration, surgery may also provide expeditious relief of edema and reduction of needs for steroids. In patients with multiple brain metastasis and mixed response to non-surgical therapy, tumor resampling may allow tissue analysis for expression of molecular tumor targets. In patients with leptomeningeal dissemination and consecutive hydrocephalus, ventriculo-peritoneal shunting improves quality of life but also allows for time to administer more therapy thus prolonging survival. Addressing the limited efficacy of many oncological drugs for brain metastases, clinical trial protocols in which surgical specimens are analyzed for pre-surgically administered agents may offer pharmacodynamic insights. Conclusion: Comprehensive neurosurgical care will have to be an integral element of multi-disciplinary oncological centres providing care to patients with brain metastases to improve on therapy and tumour biology research.